Future Opportunities and Tools for Emerging Challenges for HIV/AIDS Control - Okware, Samuel (Infectious Diseases, 2023)
This book reviews and discusses future opportunities and tools for emerging challenges in HIV/ADS control. Although significant progress has been made in the prevention, control, and care of HIV/AIDS, challenges continue to emerge. Over six sections, the book discusses a myriad of subjects, including obstacles to treatment, risk factors, demographics, testing, comorbidities, mental health, and much more.